Rakhmad Zailani Kiki (2022). Intellectual Genealogy of Betawi Ulama: Tracking the Betawi Ulama Network from the Beginning of the 19th Century to the 21st Century. Jakarta: Jakarta Islamic Centre. 213 Pages. ISBN: 978-602-98707-0-1 - Parwanto, Wendi; Utimadini, Nindya Juwita; Masrur, Imam; Ghozali, Ahmad (Journal of Al-Tamaddun, 2025)
The Center for Islamic Research and Development of Jakarta, better known as the Jakarta Islamic Centre (JIC), has in recent years become a reference point for Islamic and Betawi studies both in Indonesia and overseas. The research on the Intellectual Genealogy of the Betawi Ulama, conducted by JIC, began at the end of 2006 and continued until 2017, including visits to primary sources of information. This research extended beyond Indonesia to several countries in Southeast Asia, such as Malaysia, Singapore, Pattani in Thailand, and Cambodia, to trace the spread of Islamic da’wah. The history of Betawi is closely linked to the history of Islam in the archipelago. However, it remains minimally explored and lacks comprehensive, in-depth research by scholars, particularly concerning the intellectual genealogy of Betawi ulama.